Adat and Religious Tolerance: Ethnophilosophy Perspective - Sihol Farida Tambunan (Journal of Indonesian Social Sciences and Humanities, 2018)
As a country with the largest Muslims population in the world, Indonesia has an overwhelming number of communities with different religions, such as Protestant, Catholic, Buddhist, Hindu, Confucianism and other local religions from ancestors that influence various Indonesian people's beliefs. This situation can raise the tendency of conflicts between the majority groups of certain religions and other minority religions in Indonesia. This paper aims to explore the conditions of ethnic communities in Alor District, East Nusa Tenggara Province, who live harmoniously among different religions such as Muslims and Christians. Alor District has obtained a trophy of 'Harmony Award' 2017 from the Ministry of Religion of the Republic of Indonesia. This paper uses an ethnophilosophy perspective to find out why Alor custom or 'adat' can establish harmony among the diverse religious communities. Their custom or 'adat' as a relic of Indonesian's ancestors can play a role in avoiding the recent inter-religious conflicts that have recently sprouted in urban areas. Alors custom (adat) is one of the identity traits that had survived from the time of the ancestors of Alor people who had their local religion and before Islam and Christian became the major religions of Alor Society